Women’s empowerment in post disaster reconstruction: Perspectives on policies and frameworks - Thurairajah, Nirooja; Baldry, David (International Journal of Strategic Property Management, 2010)
There has been an increase in the occurrence of natural disasters and their impact has aroused the interest of many stakeholders to incorporate different strategies on disaster management. Although disasters may end many opportunities and lives, the lives of survivors do not cease in the disaster affected areas. The impact of natural disasters and the consequent partial reconstruction efforts have specifically presented many challenges to women. In this context, the main research investigates the empowerment of women during post disaster reconstruction particularly in Sri Lanka. Among the factors that influence women’s empowerment, existing policies and frameworks is one of the important factors that can play a major role within the post disaster reconstruction in Sri Lanka. Hence, in order to gain an understanding of the existing framework of women’s empowerment, this study investigates the national and international policies and frameworks that exist within the post disaster context in Sri Lanka. The study found that even though polices are gender neutral, they are not gender sensitive. In addition, it was found that having a single policy or framework for the whole country is unlikely to be a success, therefore, any frameworks should have room to be adopted to the local situation. First Published Online: 10 Feb 2011